Modal Sosial dan Ketahanan Ekonomi Rumah Tangga Nelayan: Studi Kasus di Desa Pesisir Kabupaten Indramayu - Ramadhani, Nadya Safitri; Rahma Prameswari, Aulia (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
Economic resilience of fisher households remains a critical issue in coastal community development, particularly in areas characterized by resource uncertainty and income fluctuation. This study aims to analyze the role of social capital in strengthening the economic resilience of fisher households in a coastal village of Indramayu Regency, Indonesia. The research adopts a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving fisher households, community leaders, and fisher group representatives. Data were analyzed using thematic analysis. The findings reveal that fisher households in Indramayu experience high economic vulnerability due to strong dependence on capture fisheries and seasonal variability. Social capital, manifested through trust, social networks, and social norms, plays a significant role in enhancing household economic resilience. Trust facilitates cooperation and informal support mechanisms, social networks expand access to information and economic resources, while social norms provide community-based social protection. Fisher households with stronger social capital demonstrate greater adaptive capacity through income diversification and collective economic strategies. However, unequal access to social capital across households was also identified, indicating disparities within the community. This study concludes that strengthening social capital is a strategic approach to improving the economic resilience of fisher households. The findings highlight the importance of community-based, inclusive coastal development policies that reinforce local social networks and institutions.